The Danube an Eminescian Obsessive Present - Golovanova, Elena (Journal of Danubian Studies and Research, 2023)
A national poet never ignores the fundamental landmarks of a people. This is also the case of Mihai Eminescu, the one who builds a series of landmarks in his own mind, which he will never give up. The first encounter of the Danube in his imagination is in national culture, where the name of the river is often mentioned. During the period of adolescent peregrination he physically meets the river; as a student in Vienna, he has numerous stops on its banks. The poetic creation has its exposed mentions, related to its grandiose symbolism. Political journalism, especially that of Timpul, has got in Eminescu an attentive and applied analyst to the political issues raised by the interests of the great powers vis-à-vis the strategic and economic potential of the Danube in general and the mouths of the Danube in particular. Taken together, all of this entitles us to speak of an eminescian obsession with the Danube.